The effectiveness of spiritual reminiscence therapy for older people with loneliness, anxiety and in Malaysia - Syed Elias, Sharifah Munirah; Neville, Christine; Scott, Theresa; Petriwskyj, Andrea (2020)
The present study aimed to determine if an SRT program is effective in reducing loneliness, anxiety and depression for older people living in a residential aged care facility in Malaysia. A randomized controlled trial design was used. The primary outcome measures were the UCLA Loneliness Scale, the Geriatric Anxiety Scale (GAS) and the Malay version of the 14-item Geriatric Depression Scale (M-GDS-14). Of 180 residents, 34 participated. The within-group analysis revealed significant mean differences for loneliness and depression. The findings suggest the value of group-based interventions for older people with loneliness and depression but were inconclusive on the effectiveness of SRT specifically.